2008
DOI: 10.1002/pola.22849
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐opening polymerization of 1,4‐dioxan‐2‐one initiated by lanthanum isopropoxide in bulk

Abstract: Lanthanum isopropoxide (La(OiPr)3) has been synthesized and employed for ring‐opening polymerization of 1,4‐dioxan‐2‐one in bulk as a single‐component initiator. The influences of reaction conditions such as initiator concentration, reaction time, and reaction temperature on the polymerization were investigated. The kinetics indicated that the polymerization is first‐order with respect to the monomer concentration. The Mechanistic investigations according to 1H NMR spectrum analysis demonstrated that the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 75 publications
(93 reference statements)
3
21
0
Order By: Relevance
“…ROPs of lactone41 and lactide37, 45 initiated by titanium alkoxides occur via a coordination‐insertion mechanism. This mechanism was proved to exist in the ROP of PDO initiated by Al(O i Pr) 3 20 and La(O i Pr) 3 33. Therefore, it is reasonable to suppose that the coordination‐insertion mechanism operates in the ROP of PDO initiated by titanium alkoxides in this study.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…ROPs of lactone41 and lactide37, 45 initiated by titanium alkoxides occur via a coordination‐insertion mechanism. This mechanism was proved to exist in the ROP of PDO initiated by Al(O i Pr) 3 20 and La(O i Pr) 3 33. Therefore, it is reasonable to suppose that the coordination‐insertion mechanism operates in the ROP of PDO initiated by titanium alkoxides in this study.…”
Section: Resultsmentioning
confidence: 65%
“…When ROP of PDO was initiated by Al(O i Pr) 3 20 and La(O i Pr) 3 ,33 there were only 1.3 effective alkoxides in both cases, which indicated that not all the three O i Pr groups are able to initiate the ROP of PDO. In this study, we have also estimated the effective alkoxide initiation sites of the individual titanium alkoxides.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…17,18 Furthermore, PPDO has proven to be tougher than PLA and even high-density polyethylene with a tensile strength of approximately 7000 psi for an ultimate elongation ranging from 500% to 600%. [21][22][23][24][25][26] Because PPDO has potential applications in the biomedical and pharmaceutical industries either as biodegradable implants or in controlled drug-delivery systems, it is necessary to remove all the traces of the metallic residues. 20 In general, PPDO can be synthesized by the ring-opening polymerization (ROP) of p-dioxanone (PDO) using metallic catalysts such as tin(II) bis(2-ethylhexanic acid), triethylaluminum, aluminum alkoxides, zinc derivatives, ferric alkoxides, titanium alkoxides, and yttrium complexes.…”
Section: Introductionmentioning
confidence: 99%